Urgensi Perlindungan Hukum terhadap Konsumen Lembaga Pinjaman Online Ilegal di Era Revolusi 4.0 - Rahmad, Tedi Sutadi; Situmeang, Ampuan; Girsang, Junimart (Jurnal Supremasi, 2024)
Online lending institution is a product of the 4.0 revolution. Its emergence has had many positive impacts on the economy, but on the other hand it has also raised several problems including misuse of personal data, intimidating collecting, and other problems caused by unlicensed or illegal online lending institutions. This study aims to identify the urgency of legal protection for consumers of illegal online lending institution.The method used in this study is normative juridical method by examining library materials or secondary data. The results showed that there are substance problems in legal protection for consumers of illegal online loan institutions in the era of revolution 4.0 which has implications for the ineffectiveness of existing regulations. Therefore, it is urgent to form new regulations that are able to regulate specifically, firmly, and thoroughly so as to create responsive laws, in order to create comfort and security for consumers of online lending institutions in Indonesia.